The Term Structure of the Spreads between Portuguese and German Interest Rates during Stage II of EMU - Fonseca, José Soares da (2002)
The spread between interest rates denominated in different currencies represents the expectations on exchange rate changes, according to the uncovered interest rate parity condition. In the present research the short- and long-term spreads between Portuguese and German Treasury bonds interest rates are studied, using weekly data covering the period from 1993-08-02 to 1998-12-14, supplied by the Banco de Portugal. The interdependence of the two spreads is estimated using cointegration methods, and their dynamic adjustment to the long-term relation is determined using impulse response analysis. The main conclusions of this research are that there was a structural break in the long-term relation between the two spreads in mid 1994, and that that relation was afterwords dominated by the consistent convergence of the Portuguese interest rates to European levels.